APAKAH FINANCIAL DISTRESS BERPERAN PADA PILIHAN AUDITOR SWICH? : A LITERATURE REVIEW - Dimas, Frezia Dimas Saputra; Sailendra; Mulyadi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study was conducted to examine the effect of audit opinion, management change and KAP reputation on the possibility of a change in public accounting firm with financial distress as a moderating variable in companies listed on the Stock Exchange. The results of previous studies show that the audit opinion variable has no effect on auditor switching, management change has no effect on auditor switching, KAP reputation does not affect auditor switching, financial distress cannot moderate the effect of auditor's opinion on auditor switching, financial distress is able to moderate management turnover on auditor switching. auditor switching, and financial distress are not able to moderate the influence of KAP reputation on auditor switching